The austere academy - Snicket, Lemony; Helquist, Brett (New York, NY : HarperCollins, 2000)
As their outrageous misfortune continues, the Baudelaire orphans are shipped off to a miserable boarding school, where they befriend the two Quagmire triplets and find that they have been followed by the dreaded Count Olaf.
Keywords: Orphans -- Fiction; Brothers and sisters -- Fiction; Boarding schools -- Fiction; Schools -- Fiction; Humorous stories